An experimental and numerical investigation of the effects of the diaphragm pressure ratio and its position on a heated shock tube performance. Issue 4 (14th February 2022) - Badri, Yousif; Elbashir, Aboubaker; Saker, Ahmad; Ahmed, Samer F.
Abstract: The main purpose of this work was to investigate the performance of heated shock tube (ST) with different pressure ratios and diaphragm positions numerically and experimentally. The numerical model was developed to simulate the fluid flow inside a shock tube test facility located at Qatar University. The shock tube was a cast‐iron hollow tube with 6 m length, 50 mm internal diameter and 10 mm thickness. ST driver and driven sections were filled with helium–argon mixture and air. The driven section was heated up to 150°C using coils. At the middle of the ST, the diaphragm was made of aluminium sheet (0.5 mm) layers. Five different pressure ratios were implemented during the experiment, and performance evaluation depended on the strength of the incident shock Mach number. The inviscid numerical model solver used transient two‐dimensional time‐accurate Navier–Stokes CFD. The model introduced a parametric study regarding three different diaphragm positions (1m, 2m and 3m) and five pressure ratios (6–10) for each position. In addition to yielding the incident and reflected wave Mach number, reflected wave temperature was also considered a shock tube performance indicator. The incident Mach numbers for the diaphragm middle position from the experiment were compared against those conducted from the model, and good matching was observed. The parametric study results showed that at high‐pressure ratios, diaphragm Positions 1 and 3 could generate a 7.4% increase in shock wave Mach number compared with the diaphragm position‐2 model. Moreover, the diaphragm position‐3 model tends to have a 2% increase in the temperature behind the reflected shock wave compared with the other two positions. Abstract : The parametric study results showed that at high‐pressure ratios, diaphragm Positions 1 and 3 are able to generate a 7.4% increase in shock wave Mach number compared with the diaphragm position‐2 model. Moreover, the diaphragm position‐3 model tends to have a 2% increase in the temperature behind the reflected shock wave compared with the other two positions.